Development of Electronic Resources on the Formation of Personal Qualities of Schoolchildren - Kanybekovna, Orynbayeva Laura; Nuralievna, Kosherbaeva Aigerim; Valerevich, Grinshkun Vadim; Yklasovich, Bidaibekov Yesen; Nuralievna, Kosherbaeva Gaziza; Bissenbayeva, Zhanat (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The new technology era is shifting the traditional ways of seeking knowledge and plays a new role in disseminating and sharing knowledge. E-learning systems have been introduced with the emergence of and developments in information technology (IT). However, most e-learning systems focus on allowing students to access and use official educational content, with less attention being paid to involve e-resources linked to curricula to support the educational process and the learners. The main objective of this research is to empower users in an e-learning environment with an Information Communication Technology (ICT) web-based system in order to play a bigger role in seeking and sharing e-resources for a better understanding of the curricula. The article focuses on the problem of teaching students in e-learning. The results of a survey helped us identify the main difficulties facing students when they begin their studies. We also describe a methodology of teaching using e-learning as web-based instruction. The use of e-learning in the educational process improves the quality of practical training and provides a better understanding of the course. This study proposes a web-based system that integrates elements of e-resources within an e-learning environment by using e-classes of 7th, 8th, and 9th grades enrolled at Secondary School as a testbed. The system deals with a set of learning cycles that support the aims of e-learning. The first cycle is the student; the second cycle is the teacher. In this study, quantitative and qualitative approaches have been used to evaluate, investigate, and compare the system's impact. The results of this study revealed that there is a significant difference between the students according to grade. Therefore, students at Secondary School would benefit from a system that exposes them to e-resources linked directly to the curriculum to achieve and navigate knowledge understanding.